Pelatihan Pengembangan Aplikasi berbasis Thunkable pada Anak Remaja di GKI Kasih Perumnas Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Citra Citra; Reva Reva (Lembaga Pengembangan Kinerja Dosen, 2025)
This training activity on application development using the Thunkable platform was designed to enhance digital literacy, logical thinking skills, and strengthen the character of adolescents through a Project-Based Learning (PjBL) approach. In today’s digital age, digital literacy is an essential competency, and equipping young people with the ability to create meaningful technology empowers them to be not just users but also creators of impactful digital solutions. The training took place on May 17, 2025, at a member’s house from the GKI Kasih congregation in Perumnas, Sorong. It was attended by 20 participants aged between 12 and 17 years. The choice of a familiar and friendly setting was intended to create a comfortable and collaborative learning environment. The training materials were structured step-by-step, starting with an introduction to the Thunkable platform, user interface (UI) design, navigation logic development using visual block programming, and culminating in group presentations and reflections on the final projects. The project theme chosen for the training was